Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities, 2018)
This issue of KIU Journal of Humanities touches on Development Administration, Civic and Political Education, Educational Administration, Judicial Administration, Social Psychology, Educational Psychology, Educational Administration, Educational Technology and Media Studies. The first part of the Journal addresses issues in Development Administration such as Sustainable Development, Fund Management, Political Economy and Foreign Direct Investments’ Framework. It is argued in one of the papers that if the quality of Almajirai and Nomadic Education Programmes is to be enhanced, then there is need for a serious commitment on the part of the government to coordinate all aspects of this education. Formal and informal stakeholders need to be involved at every stage to ensure successful value education. Government alone must not be left to the running of these model schools, all the stakeholders must be involved so as to see the end of violence in our society and equal quality education for all for sustainable all – round development in Nigeria. In part two, the importance of Civil and Political Education is emphasized. It is suggested that Civic education should be-a prime concern. There is no more important task than the development of an informed, effective, and responsible citizenry. This is because it is widely believed that democracies are sustained by citizens who have the requisite knowledge, skills, and dispositions. Absent a reasoned commitment on the part of its citizens to the fundamental values and principles of democracy, a free and open society cannot succeed. It is imperative therefore, that educators, policymakers, and members of civil society make the case and ask for the support of civic education from all segments of society and from the widest range of institutions and governments. It has been observed that the administration of justice, in all countries and at all times is a subject broad and difficult, both in its operation and its influence. It is perhaps more indicative, a truer test, of the real temper and spirit, both of the government and the people of the state or country, than any other thing. This is why the papers in part three of this edition examine the role of the judiciary as the guardian or protector and the fundamental human rights of the citizens. It has been discovered that Educational Psychology studies various factors which have impacts upon students, which may include home environment, social groupings, peer groups, his / her emotional sentiments, and mental hygiene etc.  Various methods are used in order to get the desired data about the learner in order to know about him or her mentality and behavior and its manifestations. Teacher is like a philosopher who guides his student. He is responsible to be aware about growth and development of the students. It is educational psychology which enables the teacher to use various techniques. This is the argument of one the papers in the sections that focus on social psychology, educational psychology and educational administration. A few papers in this issue highlight ideas on how students can acquire teaching and learning skills through the use of modern technologies. Based on the their findings, the papers in this section recommend among others that teachers should teach using video based instruction so as to encourage individualized learning. Also, the construction of ‘Integrated Classrooms’ that can house almost all teaching activities under one big roof is recommended. On the whole, this edition of KIU Journal of Humanities features many thought provoking articles. Some of these articles are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them. Readers are therefore advised to make proper use of the ideas presented by the various authors. Professor Oyetola O. Oniwide College of Humanities and Social Sciences, Kampala International University, P.O. Box 20000, Kampala, Uganda. editor.humanities@kiu.ac.ug March, 2018.